Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2022531890
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-25
- Filing Date
- 2021-06-16
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-06-16
AI Technical Summary
【0008】 本開示の一態様である負極によれば、電池容量と充放電サイクル特性を両立した非水電解質二次電池を提供できる。
Smart Images

Figure 0007638280000002 
Figure 0007638280000003 
Figure 0007638280000004
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery, and more particularly to a negative electrode for a non-aqueous electrolyte secondary battery containing a Si-based active material and a non-aqueous electrolyte secondary battery.
Background Art
[0002] As negative electrode active materials for non-aqueous electrolyte secondary batteries, Si-based active materials containing silicon (Si) and carbon-based active materials such as graphite are used. It is known that Si-based active materials can occlude more lithium ions per unit mass than carbon-based active materials such as graphite. In particular, a Si-based active material in which Si particles are dispersed in an oxide phase containing silicon oxide or lithium silicate is more suitable as a negative electrode active material for a non-aqueous electrolyte secondary battery because the volume change due to lithium ion occlusion is smaller than when Si is used alone. For example, Patent Document 1 discloses silicon oxide represented by SiO x (0.5 ≦ x < 1.6), and Li 2z SiO (2+z) A negative electrode active material composed of a silicon-lithium silicate composite in which a silicon phase is dispersed in a lithium silicate phase represented by (0 < z < 2) is disclosed.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] However, in non-aqueous electrolyte secondary batteries such as lithium ion batteries, it is required to maintain high charge / discharge efficiency, which is the ratio of discharge capacity to charge capacity, even after repeated charging and discharging. It is an important issue to improve the charge / discharge cycle characteristics, and it is particularly required to improve the charge / discharge cycle characteristics while increasing the capacity. The technology disclosed in Patent Document 1 does not consider the compatibility of battery capacity and charge / discharge cycle characteristics, and there is still room for improvement.
[0005] Therefore, an object of the present disclosure is to provide a negative electrode that achieves both good battery capacity and good charge / discharge cycle characteristics. [Means for solving the problem]
[0006] The negative electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a strip-shaped negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode mixture layer includes a first Si-based active material and a second Si-based active material, both of which have a structure in which Si particles are dispersed in an oxide phase, and the content of Si particles in the first Si-based active material is higher than the content of Si particles in the second Si-based active material, and the ratio of the mass of the first Si-based active material to the total mass of the first Si-based active material and the second Si-based active material is higher in the center of the negative electrode mixture layer than in the ends in the width direction of the negative electrode current collector.
[0007] A nonaqueous electrolyte secondary battery according to one aspect of the present disclosure includes the above-described negative electrode for nonaqueous electrolyte secondary batteries, a positive electrode, and a nonaqueous electrolyte. Effect of the Invention
[0008] According to the negative electrode of one aspect of the present disclosure, a nonaqueous electrolyte secondary battery that achieves both excellent battery capacity and excellent charge / discharge cycle characteristics can be provided. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery as one example of the embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that typically shows a first Si-based active material and a second Si-based active material in one example of the embodiment. [Diagram 3] FIG. 3 is a front view of a negative electrode according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body is housed in a cylindrical battery case will be exemplified below, but the electrode body is not limited to the wound type, and may be a laminated type in which multiple positive electrodes and multiple negative electrodes are alternately laminated with separators interposed therebetween. The battery case is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, or the like, or may be a pouch type composed of a laminate sheet including a metal layer and a resin layer.
[0011] Fig. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 as one example of an embodiment. In the secondary battery 10 shown in Fig. 1, an electrode body 14 and a non-aqueous electrolyte (not shown) are housed in an exterior body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. In the following description, for convenience of explanation, the sealing body 16 side will be referred to as the "upper" and the bottom side of the exterior body 15 as the "lower".
[0012] The opening end at the top of the exterior body 15 is closed by the sealing body 16, so that the inside of the secondary battery 10 is sealed. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through a through hole in the insulating plate 17 and is welded to the underside of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 and is electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 passes outside the insulating plate 18, extends to the bottom side of the exterior body 15, and is welded to the inner surface of the bottom of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal.
[0013] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the sealing of the inside of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16 and is formed, for example, by pressing a side portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.
[0014] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each member constituting the sealing body 16 has, for example, a disk shape or a ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, and the insulating member 24 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 breaks, and as a result, the upper valve body 25 swells toward the cap 26 and separates from the lower valve body 23, thereby cutting off the electrical connection between them. When the internal pressure further increases, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cap 26.
[0015] The positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte that constitute the secondary battery 10, and in particular the negative electrode active material contained in the negative electrode mixture layer that constitutes the negative electrode 12, will be described in detail below.
[0016] [Positive electrode] The positive electrode 11 has a strip-shaped positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. As shown in FIG. 1, the positive electrode 11 may have a positive electrode mixture layer 32 on both sides of the positive electrode current collector 30. As the positive electrode current collector 30, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film having the metal disposed on the surface layer, or the like can be used. The positive electrode mixture layer 32 may contain, for example, a positive electrode active material, a binder, a conductive agent, and the like. The positive electrode 11 can be manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, a binder, and the like onto the positive electrode current collector 30, drying the slurry, and then compressing the slurry to form the positive electrode mixture layer 32.
[0017] Examples of the positive electrode active material include lithium transition metal composite oxides containing transition metal elements such as Co, Mn, and Ni. Examples of the lithium transition metal composite oxide include, for example, Li x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4, Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3). These may be used alone or in combination of multiple types. In terms of achieving a higher capacity of the non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains lithium nickel composite oxides such as Li x NiO2, Li x Co y Ni 1-y O2, Li x Ni 1-y M y O z (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3). Note that inorganic compound particles such as aluminum oxide and lanthanoid-containing compounds may be adhered to the particle surface of the lithium transition metal composite oxide.
[0018] Examples of the conductive agent contained in the positive electrode binder layer 32 include carbon materials such as carbon black (CB), acetylene black (AB), ketjen black, and graphite. These may be used alone or in combination of two or more types.
[0019] Examples of the binder contained in the positive electrode mixture layer 32 include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide (PI), acrylic resins, and polyolefin resins. These may be used alone or in combination of two or more. These resins may also be used in combination with carboxymethylcellulose (CMC) or a salt thereof, polyethylene oxide (PEO), and the like.
[0020] [Negative electrode] The negative electrode 12 has a strip-shaped negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. As shown in Fig. 1, the negative electrode 12 may have a negative electrode mixture layer 36 on both sides of a negative electrode current collector 34. As the negative electrode current collector 34, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, or a film having such a metal disposed on the surface layer, can be used. The negative electrode mixture layer 36 may contain, for example, a negative electrode active material, a binder, etc.
[0021] As in the case of the positive electrode 11, the binder contained in the negative electrode mixture layer 36 may be a fluororesin such as PTFE or PVdF, PAN, PI, an acrylic resin, a polyolefin resin, or the like, but is preferably styrene-butadiene rubber (SBR). The negative electrode mixture layer may also contain CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like.
[0022] The negative electrode mixture layer 36 includes a first Si-based active material 40 and a second Si-based active material 50 as shown in FIG. 2 as negative electrode active materials (hereinafter, the first Si-based active material and the second Si-based active material may be collectively referred to as Si-based active materials). The first Si-based active material 40 includes at least an oxide phase 42 and Si particles 44, and has a structure in which the Si particles 44 are dispersed in the oxide phase 42. The first Si-based active material 40 may further include a conductive coating 48 that covers the surface of the base particle 46 composed of the oxide phase 42 and the Si particles 44. Similarly, the second Si-based active material 50 includes at least an oxide phase 52 and Si particles 54, and has a structure in which the Si particles 54 are dispersed in the oxide phase 52. The second Si-based active material 50 may further include a conductive coating 58 that covers the surface of the base particle 56 composed of the oxide phase 52 and the Si particles 54.
[0023] The Si particles 44, 54 may be approximately uniformly dispersed in the oxide phases 42, 52, respectively. That is, the mother particles 46, 56 may have a sea-island structure in which the fine Si particles 44, 54 are dispersed in the oxide phases 42, 52, respectively, and the Si particles 44, 54 may be approximately uniformly scattered in any cross section without being unevenly distributed in a certain region. The average particle size of the Si particles 44, 54 is preferably 200 nm or less, more preferably 100 nm or less. The average particle size of the Si particles 44, 54 is measured by observing the cross section of the negative electrode mixture layer using a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and specifically, the diameters of the circumscribed circles of any 100 particles selected from the SEM or TEM image are measured and the measured values are averaged.
[0024] The oxide phases 42, 52 may be mainly composed (the component with the largest mass) of a metal oxide containing at least Si. The oxide phases 42, 52 may be composed of an aggregate of particles finer than the Si particles 44, 54. The oxide phases 42, 52 may contain at least one of Li, Si, Al, and B, for example.
[0025] Before the first charge, the oxide phases 42, 52 may be mainly composed of at least one of lithium silicate and silicon oxide. The lithium silicate may be, for example, Li2z SiO (2+z) It is preferably represented by (0 < z < 2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., it is preferable that lithium silicate contains Li2SiO3 (z = 1) or Li2Si2O5 (z = 1 / 2) as a main component. When Li2SiO3 or Li2Si2O5 is used as a main component, the content of the main component is preferably more than 50% by mass, more preferably 80% by mass or more, and may be substantially 100% by mass with respect to the total mass of the oxide phases 42 and 52. Further, the silicon oxide may be, for example, silicon dioxide (SiO2). When the oxide phases 42 and 52 contain silicon dioxide as a main component, the Si-based active materials 40 and 50 have, for example, a structure in which Si particles 44 and 54 are dispersed in an amorphous SiO2 matrix, and SiO x is represented by (0.5 ≤ x ≤ 1.5). Note that SiO2 mainly changes to Li4SiO4 by the first charge.
[0026] Before the first charge, both of the oxide phases 42 and 52 may be lithium silicate phases, or both may be silicon oxide phases. However, it is preferable that the oxide phase 42 contains lithium silicate as a main component and the oxide phase 52 contains silicon oxide as a main component. That is, it is preferable that the first Si-based active material 40 is particles in which Si particles 44 are dispersed in a lithium silicate phase, and the second Si-based active material 50 is particles in which Si particles 54 are dispersed in a silicon oxide phase. In this case, the effect of improving the charge-discharge cycle characteristics of the battery becomes more remarkable.
[0027] The content of the Si particles 44 in the first Si-based active material 40 is higher than the content of the Si particles 54 in the second Si-based active material 50. Here, the content of the Si particles 44 in the first Si-based active material 40 means the ratio of the mass of the Si particles 44 to the mass of the base particle 46, and is preferably 40 mass% to 70 mass%, and more preferably 40 mass% to 60 mass%. Moreover, the content of the Si particles 54 in the second Si-based active material 50 means the ratio of the mass of the Si particles 54 to the mass of the base particle 56, and is preferably 20 mass% to 40 mass%, and more preferably 25 mass% to 35 mass%. For example, the content of the Si particles 44 in the first Si-based active material 40 can be 40 mass% or more, and the content of the Si particles 54 in the second Si-based active material 50 can be less than 40 mass%.
[0028] The Si-based active materials 40, 50 may be composed of only the base particles 46, 56, respectively, or may have a conductive coating 48, 58 composed of a material having a higher conductivity than the oxide phases 42, 52 on the surface of the base particles 46, 56. The conductive material constituting the conductive coating 48, 58 may be at least one selected from the group consisting of carbon materials, metals, and metal compounds, and it is preferable to use a carbon material. Examples of methods for carbon-coating the surface of the base particles 46, 56 include a CVD method using acetylene, methane, etc., and a method of mixing coal pitch, petroleum pitch, phenolic resin, etc. with the base particles 46, 56 and performing a heat treatment. In addition, a carbon coating layer may be formed by fixing a conductive agent such as carbon black or ketjen black to the surface of the base particles 46, 56 using a binder.
[0029] The conductive coatings 48, 58 may be formed to cover substantially the entire surface of the base particles 46, 56. The thickness of the conductive coatings 48, 58 is preferably 1 nm to 200 nm, more preferably 5 nm to 100 nm, in consideration of ensuring electrical conductivity and diffusibility of lithium ions to the base particles 46, 56. If the conductive coatings 48, 58 are too thin, the electrical conductivity decreases and it becomes difficult to uniformly coat the base particles 46, 56. On the other hand, if the conductive coatings 48, 58 are too thick, the diffusion of lithium ions to the base particles 46, 56 tends to be hindered, resulting in a decrease in capacity. The thickness of the conductive coatings 48, 58 can be measured by observing the cross section of the particle using a SEM, a TEM, or the like.
[0030] The volume-based median diameter (D50) of the first Si-based active material 40 and the D50 of the second Si-based active material 50 may be, for example, 2 μm to 20 μm. Here, the volume-based median diameter (D50) is a particle diameter at which the volume accumulated value is 50% in a particle size distribution measured by a laser diffraction scattering method, and is also called a 50% particle diameter or a median diameter. The D50 of the first Si-based active material 40 may be larger than the D50 of the second Si-based active material 50. In this case, the D50 of the first Si-based active material 40 is preferably 7 μm to 20 μm, more preferably 8 μm to 15 μm. The D50 of the second Si-based active material 50 is preferably 2 μm to 7 μm, more preferably 3 μm to 6 μm. The D50 of the Si-based active materials 40 and 50 may be smaller than the D50 of a carbon-based active material described later.
[0031] The Si-based active materials 40, 50 can be manufactured, for example, through the following steps 1 to 3. (1) Si particles and an inorganic compound containing Si, such as lithium silicate or silicon oxide, are mixed in a predetermined mass ratio. The inorganic compound becomes the oxide phases 42, 52. When the first Si-based active material 40 is manufactured, the mixing ratio of Si particles is made higher than when the second Si-based active material 50 is manufactured. (2) The raw material powder is pulverized and mixed in an inert atmosphere using a ball mill or the like, and then heat-treated (sintered), for example, at 500° C. to 700° C. The sintered body is pulverized and classified so that D50 falls within a predetermined range, thereby obtaining mother particles 46, 56 in which Si particles 44, 54 are dispersed in oxide phases 42, 52. (3) Next, the base particles 46, 56 are mixed with a carbon material such as coal pitch and heat-treated in an inert atmosphere to obtain the Si-based active materials 40, 50 having conductive coatings 48, 58 such as carbon coatings formed on the surfaces of the base particles 46, 56.
[0032] The Si-based active materials 40 and 50 can absorb more lithium ions than carbon-based active materials, and therefore the capacity of the battery can be increased by using the Si-based active materials 40 and 50 as the negative electrode active material. The Si-based active materials 40 and 50 undergo a larger volume change during charging and discharging than carbon-based active materials, and therefore it is preferable to use the carbon-based active material and the Si-based active material 40 and 50 in combination.
[0033] As the carbon-based active material, graphite that has been conventionally used as a negative electrode active material, such as natural graphite such as flake graphite, lump graphite, and amorphous graphite, as well as artificial graphite such as lump graphite (MAG) and mesocarbon microbeads (MCMB), can be used. The D50 of the graphite may be, for example, 18 μm to 24 μm.
[0034] The content of the Si-based active material 40, 50 is preferably 2 mass% to 20 mass%, more preferably 3 mass% to 15 mass%, and particularly preferably 4 mass% to 10 mass% based on the total mass of the negative electrode active material. That is, the mixing ratio of the carbon-based active material and the Si-based active material is preferably 98:2 to 80:20 by mass, more preferably 97:3 to 85:15, and particularly preferably 96:4 to 90:10. If the mass ratio of the carbon-based active material and the Si-based active material 40, 50 is within this range, it becomes easy to achieve a high capacity and to more significantly improve the charge-discharge cycle characteristics.
[0035] Next, the distribution of the negative electrode active material in the negative electrode mixture layer 36 formed on the surface of the negative electrode current collector 34 will be described with reference to Fig. 3. Fig. 3 is a front view of the negative electrode 12 according to one embodiment, in which the end portions 34a are regions at both ends in the width direction of the strip-shaped negative electrode current collector 34, and the central portion 34b is a central region in the width direction of the negative electrode current collector 34. The ratio of the lengths in the width direction (hereinafter referred to as width) of one end portion 34a, the central portion 34b, and the other end portion 34a can be, for example, 1:8:1 to 3:4:3.
[0036] In the negative electrode mixture layer 36, the ratio of the mass of the first Si-based active material 40 to the total mass of the first Si-based active material 40 and the second Si-based active material 50 is larger in the central portion 34b than in the end portion 34a. As a result, the central portion 34b, where the negative electrode potential is lower than that of the end portion 34a due to repeated charging and discharging, contains a large amount of the first Si-based active material 40, thereby reducing the charge and discharge depth of the first Si-based active material 40 and suppressing side reactions, thereby improving the charge and discharge cycle characteristics. The first Si-based active material 40 with a high content of Si particles 44 is advantageous for increasing the capacity, but it expands and contracts greatly during charging and discharging, and side reactions are likely to occur on the surface. The negative electrode 12 expands and contracts due to charging and discharging, and the electrolyte is repeatedly introduced and discharged, and a concentration gradient of lithium ions in the electrolyte is generated in the inside of the electrode body 14 along the width direction of the negative electrode current collector 34, and the concentration of lithium ions in the electrolyte is higher in the central portion 34b than in the end portion 34a. Due to this lithium ion concentration gradient, the negative electrode potential during charging and discharging is higher at the end portion 34a and lower at the central portion 34b. Therefore, by disposing a larger amount of the first Si-based active material 40 in the central portion 34b, where side reactions are less likely to occur, it is possible to achieve both high capacity and good charge-discharge cycle characteristics.
[0037] The negative electrode 12 can be produced, for example, through the following steps 1 to 3. (1) A first Si-based active material 40 and a second Si-based active material 50 are mixed to prepare an Si-based active material A having a high mass ratio of the first Si-based active material 40 to the total mass of the first Si-based active material 40 and the second Si-based active material 50, and an Si-based active material B having a low mass ratio. Note that the Si-based active material A may substantially contain only the first Si-based active material, and the Si-based active material B may substantially contain only the second Si-based active material. (2) An Si-based active material A and a carbon-based active material are mixed in an appropriate ratio to prepare a negative electrode active material A, which is then mixed with a binder, a thickener, etc. in an appropriate ratio to prepare a negative electrode mixture slurry A using water as the dispersion medium. Similarly, an Si-based active material B and a carbon-based active material are mixed in an appropriate ratio to prepare a negative electrode active material B, which is then mixed with a binder, a thickener, etc. in an appropriate ratio to prepare a negative electrode mixture slurry B using water as the dispersion medium. (3) On the surface of the negative electrode current collector 34, the negative electrode mixture slurry A is applied to the central portion 34b, dried, and then the negative electrode mixture slurry B is applied to the end portion 34a, dried, and compressed to form the negative electrode mixture layer 36, thereby manufacturing the negative electrode 12. Note that after the negative electrode mixture slurry A is applied, the negative electrode mixture slurry B may be applied without drying, and then dried and compressed to form the negative electrode mixture layer 36. Alternatively, the negative electrode mixture slurry B may be applied to the end portion 34a, and then the negative electrode mixture slurry A may be applied to the central portion 34b.
[0038] [Separator] As the separator 13, a porous sheet having ion permeability and insulating properties can be used. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, and the like are suitable. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator 13.
[0039] [Non-aqueous electrolyte] The non-aqueous electrolyte may include a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent that can be used include esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a portion of the hydrogen of these solvents is substituted with a halogen atom such as fluorine. Examples of the halogen-substituted product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).
[0040] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.
[0041] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxy Examples of chain ethers include ethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.
[0042] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), imide salts such as LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, etc. The lithium salt may be used alone or in combination of multiple kinds. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., it is preferable to use LiPF6. The concentration of the lithium salt may be, for example, 0.8 mol to 1.8 mol per 1 L of the non-aqueous solvent.
Examples
[0043] Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.
[0044] <Examples> [Fabrication of positive electrode] As the positive electrode active material, LiNi 0.91 Co 0.045 Al 0.045Lithium nickelate containing cobalt and aluminum represented by O2 was used. The positive electrode active material, acetylene black (AB), and polyvinylidene fluoride (PVdF) were mixed at a mass ratio of 100:0.75:0.6 to prepare a positive electrode binder slurry using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. The positive electrode binder slurry was applied to both sides of a long positive electrode current collector made of aluminum foil by the doctor blade method. After drying the coating film, the coating film was compressed with a roller to form a positive electrode binder layer on both sides of the positive electrode current collector. The positive electrode current collector with the positive electrode binder layer formed was cut into a predetermined electrode size to fabricate a positive electrode.
[0045] [Preparation of the First Si-Based Active Material] In an inert atmosphere, Si particles (3N, pulverized product with a particle size of 10 μm) and Li 2z SiO (2+z) lithium silicate particles (pulverized product with a particle size of 10 μm) represented by (0 < z < 2) were mixed so that the content rate of the Si particles was 52% by mass, and the mixture was pulverized by a ball mill. Then, the mixed powder was taken out in an inert atmosphere and heat-treated under the conditions of 600 °C and 4 hours in an inert atmosphere. The heat-treated powder (hereinafter referred to as mother particles) was pulverized by a jet mill and then mixed with coal pitch, and heat-treated under the conditions of 800 °C and 5 hours in an inert atmosphere to form a conductive carbon film on the surface of the mother particles. The coating amount of carbon is 2% by mass based on the total mass of the particles including the mother particles and the conductive film. The particles with the conductive film formed were crushed and classified using a sieve to obtain a first Si-based active material with a D50 of 11 μm in which Si particles were dispersed at a content rate of 52% by mass in the lithium silicate phase.
[0046] [Preparation of the Second Si-Based Active Material] In an inert atmosphere, Si particles (3N, 10 μm crushed product) and silicon dioxide particles (10 μm crushed product) were mixed so that the content of Si particles was 30 mass%, and crushed with a ball mill. Then, the mixed powder was taken out in an inert atmosphere, and heat-treated under the condition of 600 ° C and 4 hours in an inert atmosphere. The heat-treated powder (hereinafter referred to as mother particles) was crushed with a jet mill, and then a conductive carbon coating was formed on the surface of the mother particles by a CVD method (1000 ° C). The amount of carbon coating was 5 mass % with respect to the total mass of the particles including the mother particles and the conductive coating. The particles on which the conductive coating was formed were crushed and classified using a sieve to obtain a second Si-based active material in which Si particles were dispersed in a silicon dioxide phase at a content of 30 mass % and D50 was 5 μm.
[0047] [Analysis of Si-based active materials] The particle cross-sections of the Si-based active materials were observed by SEM, and it was confirmed that the Si particles were dispersed almost uniformly in the oxide phase in all cases. The average particle size of the Si particles was less than 50 nm in all cases. The carbon coating amount was analyzed by a CS analyzer. The D50 of the Si-based active materials was measured using a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-2000A). The measurements were performed using water as the dispersion medium and a particle refractive index of 1.70-0.01i.
[0048] [Preparation of negative electrode] A mixture of graphite with a D50 of 22 μm and the first Si-based active material in a mass ratio of 91.7:8.3 was used as negative electrode active material A. Negative electrode active material A, carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 100:1:1:1 to prepare negative electrode mixture slurry A using water as a dispersion medium.
[0049] A mixture of graphite having a D50 of 22 μm and the second Si-based active material in a mass ratio of 96.2:3.8 was used as negative electrode active material B. Negative electrode mixture slurry B was prepared in the same manner as for the preparation of negative electrode mixture slurry A, except that negative electrode active material B was used instead of negative electrode active material A.
[0050] A negative electrode current collector made of copper foil was prepared, and the end, center, and end portions were arranged in a length ratio of 2:6:2 in the width direction. The negative electrode mixture slurry A was applied to the center of both sides of the negative electrode current collector by the doctor blade method, and the coating was dried. After that, the negative electrode mixture slurry B was applied to both ends by the doctor blade method, and the coating was dried and compressed with a roller to form a negative electrode mixture layer on both sides of the negative electrode current collector. The negative electrode current collector on which the negative electrode mixture layer was formed was cut to a predetermined electrode size to prepare a negative electrode.
[0051] [Preparation of non-aqueous electrolyte] LiPF6 was dissolved at a concentration of 1.3 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 20:5:75 (25°C, 1 atm). Furthermore, vinylene carbonate (VC) was dissolved at a concentration of 4 mass% in the mixed solvent to prepare a non-aqueous electrolyte (electrolytic solution).
[0052] [Preparation of secondary battery] An aluminum lead was attached to the positive electrode, and a nickel lead was attached to the negative electrode, and the positive electrode and the negative electrode were spirally wound with a separator made of a microporous polyethylene film between them to prepare a wound electrode body. This electrode body was housed in an outer casing, and the nickel lead was welded to the bottom of the outer casing. Next, the aluminum lead was welded to a seal, and the above-mentioned electrolyte was injected, and the opening of the outer casing was sealed with a seal to obtain a nonaqueous electrolyte secondary battery.
[0053] <Comparative Example 1> In the preparation of the negative electrode, a mixture of graphite, a first Si-based active material, and a second Si-based active material in a mass ratio of 93.5:5:1.5 was used as the negative electrode active material C. A negative electrode mixture slurry C was prepared using the negative electrode active material C instead of the negative electrode active material A, and the negative electrode mixture slurry C was applied to the entire surface of the center and both ends of the negative electrode current collector to form a negative electrode mixture layer. Except for this, a negative electrode was prepared in the same manner as in the examples, and a nonaqueous electrolyte secondary battery was prepared.
[0054] <Comparative Example 2> In the preparation of the negative electrode, a mixture of graphite and a second Si-based active material in a mass ratio of 97.5:2.5 was used as the negative electrode active material D, and a mixture of graphite and a first Si-based active material in a mass ratio of 87.5:12.5 was used as the negative electrode active material E. Except for the fact that the negative electrode mixture slurry D was prepared using the negative electrode active material D instead of the negative electrode active material A, and the negative electrode mixture slurry E was prepared using the negative electrode active material E instead of the negative electrode active material B, the negative electrode was prepared in the same manner as in the examples, and a nonaqueous electrolyte secondary battery was prepared.
[0055] <Comparative Example 3> In the preparation of the negative electrode, a mixture of graphite and a second Si-based active material in a mass ratio of 94:6 was used as negative electrode active material F. A negative electrode mixture slurry F was prepared using negative electrode active material F instead of negative electrode active material A, and the negative electrode mixture slurry F was applied to the entire surface of the center and both end portions of the negative electrode current collector to form a negative electrode mixture layer. Except for this, a negative electrode was prepared in the same manner as in the Examples, and a nonaqueous electrolyte secondary battery was prepared.
[0056] The initial discharge capacity and charge / discharge cycle characteristics of each battery were evaluated by the following method. The charge / discharge cycle characteristics were evaluated by using the number of cycles at which the discharge capacity suddenly dropped as an index, and the relative value of each battery is shown when the number of cycles at which the discharge capacity suddenly dropped in the example is set to 100. Table 1 shows the evaluation results, as well as the composition (mass ratio) of the negative electrode active material at the end and center of the negative electrode, and the average composition of the entire negative electrode mixture layer.
[0057] [Evaluation of initial discharge capacity] Each battery in the Examples and Comparative Examples was charged at a constant current of 0.3 C in a temperature environment of 25° C. until the battery voltage reached 4.2 V, then charged at a constant voltage until the current value at 4.2 V reached 1 / 50 C, and then discharged at a constant current of 0.5 C until the battery voltage reached 2.85 V. The discharge capacity at this time was defined as the initial discharge capacity.
[0058] [Evaluation of charge / discharge cycle characteristics] Each battery in the examples and comparative examples was charged at a constant current of 0.3 C in a temperature environment of 25° C. until the battery voltage reached 4.2 V, then charged at a constant voltage until the current value at 4.2 V reached 1 / 50 C, and then discharged at a constant current of 0.5 C until the battery voltage reached 2.85 V. This constitutes one cycle of charging and discharging, and the charge / discharge efficiency, which is the ratio of the discharge capacity to the charge capacity, was calculated for each cycle. The number of cycles at which the charge / discharge efficiency fell below 99.8% after five consecutive cycles was determined as the number of cycles at which the discharge capacity suddenly dropped. Batteries with a large number of cycles at which the discharge capacity suddenly dropped maintained a high charge / discharge efficiency and had good charge / discharge cycle characteristics.
[0059] [Table 1]
[0060] As shown in Table 1, the battery of the Example has superior charge-discharge cycle characteristics compared to the batteries of Comparative Examples 1 and 2, and exhibits a higher capacity compared to Comparative Example 3. Thus, while the batteries of Comparative Examples 1 to 3 are insufficient in either the battery capacity or the charge-discharge cycle characteristics, only the battery of the Example achieves both the battery capacity and the charge-discharge cycle characteristics. In other words, in order to achieve both the battery capacity and the charge-discharge cycle characteristics, it is necessary not only to mix two types of Si-based active materials (a first Si-based active material and a second Si-based active material) having different contents of Si particles, but also to appropriately arrange each of them in the negative electrode mixture layer. [Explanation of symbols]
[0061] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 exterior body, 16 sealing body, 17, 18 insulating plate, 19 positive electrode lead, 20 negative electrode lead, 21 grooved portion, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cap, 26a opening, 27 gasket, 30 positive electrode current collector, 32 positive electrode mixture layer, 34 negative electrode current collector, 34a end portion, 34b center portion, 36 negative electrode mixture layer, 40 first Si-based active material, 50 second Si-based active material, 42, 52 oxide phase, 44, 54 Si particles, 46, 56 mother particles, 48, 58 conductive coating
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: a strip-shaped negative electrode current collector; and a negative electrode mixture layer formed on a surface of the negative electrode current collector, The negative electrode mixture layer includes a first Si-based active material and a second Si-based active material, The first Si-based active material and the second Si-based active material each have a structure in which Si particles are dispersed in an oxide phase, and the content of the Si particles in the first Si-based active material is higher than the content of the Si particles in the second Si-based active material; a ratio of a mass of the first Si-based active material to a total mass of the first Si-based active material and the second Si-based active material in the negative electrode mixture layer is larger in a central portion than in end portions in a width direction of the negative electrode current collector.
2. 2 . The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein before an initial charge, the oxide phase is mainly composed of at least one of lithium silicate and silicon oxide.
3. Before the first charge, The oxide phase of the first Si-based active material is mainly composed of the lithium silicate, 3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 2, wherein the oxide phase of the second Si-based active material is mainly composed of silicon oxide.
4. A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of claims 1 to 3, a positive electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Negative electrode for lithium secondary battery and lithium secondary battery using it
JP2007317415A
Nonaqueous electrolyte secondary battery
JP2019091615A
Non-aqueous electrolyte secondary battery
WO2019142744A1
Nonaqueous electrolyte secondary battery negative electrode and nonaqueous electrolyte secondary battery
WO2020066576A1